Molecular and biological characterization of selected sweet potato feathery mottle virus (SPFMV) strains in the Philippines (2012)
Three sweet potato feathery mottle virus (SPFMV) strains were identified based on biological and molecular properties of eight SPFMV isolates that were obtained from some sweet potato growing areas in Luzon, Visayas and Mindanao. The different SPFMV isolates caused different reactions to Chenopodium species. Six of the 8 SPFMV isolates caused local lesions to different Chenopodium species, while only the Tranca isolate induced local lesions to C. amaranticolor. The different isolates caused various symptoms ranging from vein clearing, mottling, mosaic, feathering and leaf curls on Ipomoea setosa and I. nil. Phylogenetic analysis of the amino acid (aa) sequences of the Philippine SPFMV isolates along with the other known aa sequences from the GenBank database indicates the occurrence of at least three strains of SPFMV, namely: the Common strain (Saysain and Binukawan); the East African (Tranca isolate); and the Russet Crack strain (RC) (Sapang, Nagbunga, Visca, Luksuhin and Dalwangan isolates), the latter, being observed as the predominant SPFMV strain occurring in the Philippines. Knowledge on the presence of these different SPFMV strains offers a high significant contribution in the deployment of our local sweet potato varieties and in breeding for virus resistance.